Collection network design with capacity planning in reverse logistics: static and restricted-dynamic models. Issue 8 (3rd August 2019) - Kim, Ji-Su; Lee, Dong-Ho
ABSTRACT: This study proposes two collection network design models that determine the locations and capacities of collection centres and the allocations of refuse at demand points to the opened collection centres: a single-period static model for time-invariant demands and a multi-period restricted-dynamic model for time-variant demands over a planning horizon. The capacities of collection centres are not given, but decision variables are used to obtain cost savings by minimizing surplus capacities. The maximum allowable distance between collection centres and demand points and the minimum recovery rates of collection centres are also considered. Two heuristics are proposed for each of the two problems after formulating them as integer programming models. Computational experiments were conducted on various test instances, and the results are reported. It is shown from the test results that the restricted-dynamic approach outperforms the static model significantly when the refuse demands are time variant. Finally, some managerial insights are derived.